Estimation of Apolipoprotein A1, Haptoglobin and Alpha 2macroglobulin with some Biochemical Metabolic Markers in Nonalcoholic Fatty Liver Disease Iraqi Patients - hiba abid Al-hussein hassan; Dawood Salman Dawood; Raghad Jawad Hussein (Journal of Techniques)
"non-alcoholic fatty liver disease" starts with hepatic lipid accumulation and is a dangerous factor for disease development.